2007
DOI: 10.1111/j.1750-3841.2007.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Overall Quality of Table Grapes Stored under Modified Atmosphere Packaging in Combination with Natural Antimicrobial Compounds

Abstract: Consumers demand new means of preservation with absence of chemicals. In this work a package was developed (thermosealed baskets) with grapes wrapped with 2 distinct films (M and P) with different permeability (medium and high, respectively) without or with the addition of a mixture of eugenol, thymol, and carvacrol. Table grapes stored on air (control) lost their quality attributes very rapidly, manifested by accelerated weight loss, color changes, softening, and increase in soluble solids concentration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 31 publications
8
45
0
Order By: Relevance
“…The effectiveness of pure (alone) constituents of thymol and carvacrol as the major constituents of thyme and summer savory oils, respectively in reduction of postharvest fungal decay in Valero et al 2006;Guillén et al 2007). Also Liu et al (2005) reported that fumigation of plums with thymol reduced brown rot incidence in treated fruits in comparison with control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of pure (alone) constituents of thymol and carvacrol as the major constituents of thyme and summer savory oils, respectively in reduction of postharvest fungal decay in Valero et al 2006;Guillén et al 2007). Also Liu et al (2005) reported that fumigation of plums with thymol reduced brown rot incidence in treated fruits in comparison with control.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of essential oils against a large number of phytopathogenic fungi under in vitro conditions is well documented (Bouchra et al 2003;Boyraz and Özcan 2006;Viuda-Martos et al 2007). But, a few studies in the case of the efficacy of essential oils and constituents to control of postharvest pathogens and maintain quality of some fruit and vegetables such as strawberry, apple, cherry tomato, table grape were investigated (Reddy et al 1998;Martinez-Romero et al 2004;Valero et al 2006;Guillén et al 2007;Lee et al 2007;Tripathi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of MAP on restriction of berry decay was lower than that of honey in terms of magnitude. This is most likely because grapes are nonclimacteric fruits with low respiration intensity, and thus the concentration of CO 2 inside MAP were not high enough to act as fungicide (Guillén et al 2007).…”
Section: Decay Browning and Shriveling Ratesmentioning
confidence: 99%
“…These data are supported by results from eugenol, menthol and thymol treatments, which reduced the rate of rachis deterioration and suggest that such effects could be produced in part by an antioxidant effect of these compounds (Valverde et al, 2005a). In addition, Guillén et al (2007), using essential oils and modified atmospheric conditions to maintain the quality of table grapes, concluded that the antioxidant capacity of the essential oils helped to prevent the deterioration by oxidation that occurs in senescence. Therefore, the possibility that the phenolic compounds naturally found in rachises participate in a ROS defense process is plausible.…”
Section: Discussionmentioning
confidence: 65%